Knowledge of Farmers on Functioning of e-NAM - Raju, M. Shanmukh; Devy, M. Rama; Gopal, P. V. Sathya (Indian Journal of Extension Education, 2022)
National Agriculture Market (e-NAM) is a pan-India electronic trading portal that networks the existing APMC mandis to create a unified national market for agricultural commodities. The study investigated the knowledge level of e-NAM registered farmers about the features and functioning of e-NAM in Duggirala market of Andhra Pradesh during 2019-2020. A total sample of 120 farmers was randomly selected from six mandals viz. Kollur, Kollipara, Bhattiprolu, Tenali, Mangalagiri and Duggirala of Guntur district in Andhra Pradesh. The data were collected with pre-structured interview schedule. The knowledge on functioning of e-NAM was measured in three phases viz. gate entry, quality assaying and e-bidding. Majority of the farmers had knowledge on details of registration fee, details of quality assaying fee and provision of choice to accept or reject the bid in the gate entry, quality assaying and e-bidding phases of e-NAM respectively. Further, it was observed that majority of the farmers had medium level of knowledge on functioning of e-NAM. Knowledge scores were significantly related with education, extension contact, market orientation, income orientation, mass media exposure, risk orientation and social participation. All the selected eleven variables of the profile put together explained about 59.90 per cent variation in the knowledge of respondents. There is a large scope for imparting training to the farmers about various aspects of e-NAM in order to enhance its utilization effectively and efficiently.
Keywords: e-NAM registered farmers; Knowledge; Awareness; APMC; Market and Functioning